The Impact of Digital Economy Development and Its Effect on the Income of Micro, Small and Medium Enterprises Actors - Eliana Eliana; Hapsari Widayani; Andika Isma (Indonesian Journal of Business and Entrepreneurship Research, 2023)
This research was conducted with the aim of knowing how the impact of the development of the Digital Economy and its influence on the income of MSME Business Actors in Makassar City. The research method used is descriptive qualitative research, the way data is collected is through observation, interviews, questionnaires and documentation. The informants in this study were MSME business actors in Makassar City, totaling 96 entrepreneurs as research objects. The results of this study indicate a positive and significant effect of the digital economy on the income of MSME business actors in Makassar City. While the factors that support and hinder the MSME sector in the perspective of the digital economy are the ability to know the use of technological media which is a supporting indicator of the success of the digtal economy. The development of the digital economy is an important factor in the success of a business, therefore it is necessary to increase knowledge about the digital economy for business actors so that in running their business there is an increase in terms of allocating good income for future businesses and also by better mastering emerging digital technology in order to attract customers from various regions and be more efficient in promoting their products.